2016
DOI: 10.1080/1120009x.2016.1156893
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic consumption in Turkish hospitals; a multi-centre point prevalence study

Abstract: This multi-centre study aimed to determine the antibiotic consumption in Turkish hospitals by point prevalence. Antibiotic consumption of 14 centres was determined using the DDD method. Among hospitalized patients, 44.8% were using antibiotics and the total antibiotic consumption was 674.5 DDD/1000 patient-days (DPD). 189.6 (28%) DPD of the antibiotic consumption was restricted while 484.9 (72%) DPD was unrestricted. Carbapenems (24%) and beta lactam/beta lactamase inhibitors (ampicillin-sulbactam or amoxicill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
28
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 15 publications
1
28
1
Order By: Relevance
“…The reason behind such high rates of resistance is that only the XDR and MDR isolates were selected for this study. Moreover, a study on antibiotic consumption among patients, hospitalized in Turkey, showed that 44.8% of them were using antibiotics and the total antibiotic consumption was 674.5 defined daily dose/1000 patient-days [18]. Therefore, it is highly possible that a high rate of resistance is associated with antibiotic consumption.…”
Section: Discussionmentioning
confidence: 99%
“…The reason behind such high rates of resistance is that only the XDR and MDR isolates were selected for this study. Moreover, a study on antibiotic consumption among patients, hospitalized in Turkey, showed that 44.8% of them were using antibiotics and the total antibiotic consumption was 674.5 defined daily dose/1000 patient-days [18]. Therefore, it is highly possible that a high rate of resistance is associated with antibiotic consumption.…”
Section: Discussionmentioning
confidence: 99%
“…In Turkey, 71.3% of patients in ICUs are treated with antibiotics [2]. This widespread use is unnecessary and inappropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Keywords: Antibiotic stewardship, rational antibiotic use, antibiotic resistance, gram positive microorganisms, inappropriate antibiotic use Background Infection development is an important cause of morbidity and mortality in intensive care units (ICUs), leading to the widespread use of antibiotics [1]. {, #1@@hidden}{Kallen, 2018 #382}{, 2018 #382} {Kallen, 2018 #404}It is reported that 41-85% of ICU patients use at least one antibiotic and antibiotic consumption is 10 times higher in ICUs compared to other units [2]. This widespread usage increases the unnecessary and inappropriate use of antibiotics and causes an increase in antimicrobial resistance [3].…”
mentioning
confidence: 99%
See 2 more Smart Citations